2005
DOI: 10.1111/j.1464-410x.2005.05343.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of dose titration with darifenacin, an M3‐selective receptor antagonist

Abstract: electronic daily diary. Safety and tolerability were evaluated from withdrawal rates and adverse-event reports. RESULTSThe treatment groups had comparable baseline characteristics. Similar proportions of darifenacin (59%) and placebo (68%) recipients increased the dose at 2 weeks; at 12 weeks patients on darifenacin (overall group) had a significantly greater reduction in the median number of incontinence episodes per week than had those on placebo, at -8.2 ( -62.9%) and -6.0 ( -48.1%), respectively ( P = 0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 14 publications
7
72
0
1
Order By: Relevance
“…treatment with darifenacin 3.75, 7.5, or 15 mg, or matching placebo. 16,17 Details of the design and methodology for the extension study have previously been reported elsewhere. 13 During the open-label extension, patients received darifenacin 7.5 mg (irrespective of feeder-study dose) for the first 2 weeks, followed by individualized dose adjustments (7.5 or 15 mg o.d.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…treatment with darifenacin 3.75, 7.5, or 15 mg, or matching placebo. 16,17 Details of the design and methodology for the extension study have previously been reported elsewhere. 13 During the open-label extension, patients received darifenacin 7.5 mg (irrespective of feeder-study dose) for the first 2 weeks, followed by individualized dose adjustments (7.5 or 15 mg o.d.)…”
Section: Methodsmentioning
confidence: 99%
“…13 As in the feeder studies, the use of concomitant medications (such as anticholinergic/antispasmodic drugs, opioids and other drugs known to cause constipation) was restricted, and patients taking potent inhibitors of cytochrome P450 3A4 were required to receive a maximum dose of 7.5 mg darifenacin. In addition, patients with clinically significant hepatic impairment or moderate hepatic impairment (ChildPugh B) 16,17 were excluded. Changes in the active management of OAB (such as introduction of a bladder training program) were not permitted during this study.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles [19][20][21] not specifying adverse events, one article [22] not differentiating adverse events between antimuscarinic and placebo, six articles [23][24][25][26][27][28] not discriminating adverse events between different fixed dosages, and three articles [29][30][31] only comparing different releases within the same antimuscarinic and dosage were excluded. Thus, we finally included 69 trials including one report [66] with two different age strata ( Table 2, Data S2).…”
Section: Resultsmentioning
confidence: 99%
“…12 In the pooled analysis, a total of 1059 patients (85 per cent women, 95 per cent idiopathic OAB) with frequency, urgency and urge incontinence of at least six months' duration were randomised to placebo or darifenacin 7.5 or 15mg per day. The primar y end-point was the median change in number of incontinence episodes per week.…”
Section: Clinical Trialsmentioning
confidence: 99%